US Foreign Policy to South America since 9/11: Neglect or Militarisation? - Milani, Livia Peres [UNESP] (Pontifícia Universidade Católica do Rio de Janeiro, Instituto de Relações Internacionais, 2021)
Academic literature on US Foreign Policy to South America usually states its lack of attention to the region in the post 9/11 period. I aim to problematize this assertion through an analysis of US regional security policy. Therefore, I consider data referring to military and economic assistance, arms transfers, and the SOUTHCOM position towards its area of responsibility, as well as official documents and diplomatic cables. I conclude that, although the region was not a priority, a waning in US actions or a moment of neglect in its policy towards it was likewise not observed. From a historical perspective, the area was never the main focus of attention, but there is a specialized bureaucracy that works on the region to maintain US hegemony. Therefore, the investigation indicates that Latin American assertiveness during the 2000s was caused primarily by the conjunction of the ascension of leftist governments and quest for autonomy, as well as by Chinese and Russian involvement in Latin America, but not by US neglect. The article is divided into six sections, including the introduction and final remarks. Following the introduction, I analyse the academic literature regarding USA-Latin American relations in the second section, the US assistance in the third, the SOUTHCOM postures in the fourth, and the strategies deployed by the USA regarding great powers and arms transfers in the fifth. Finally, I present the final remarks.

A literatura acadêmica sobre a política externa dos EUA para a América do Sul geralmente afirma uma falta de atenção para esta região no período pós-11 de setembro. Pretendo problematizar essa afirmação por meio de uma análise da política de segurança regional dos Estados Unidos. Considero os dados referentes à assistência militar e econômica, transferência de armas e a posição do SOUTHCOM em relação à sua área de responsabilidade, bem como documentos oficiais e cabos diplomáticos. Concluo que, embora a região não tenha sido uma prioridade, não houve um enfraquecimento das ações dos Estados Unidos ou um momento de abandono. Do ponto de vista histórico, a área nunca foi o foco principal das atenções, mas há uma burocracia especializada que trabalha para manter a hegemonia dos EUA. Portanto, a investigação indica que a assertividade latino-americana durante os anos 2000 foi causada principalmente pela conjunção da ascensão dos governos de esquerda e centro-esquerda e pela busca por autonomia e envolvimento chinês e russo na América Latina, não por negligência dos EUA. O artigo está dividido em seis seções, incluindo a introdução e as considerações finais. Após a introdução, a segunda seção é dedicada à análise da literatura acadêmica, a terceira ao estudo da assistência dos Estados Unidos, a quarta examina as posturas do SOUTHCOM e a quinta seção investiga as estratégias dos Estados Unidos em relação a grandes potências e transferências de armas. Finalmente, as considerações finais são apresentadas.
Política Externa dos EUA para a América do Sul desde o 11 de Setembro: Negligência ou Militarização?
Keywords: : USA-Latin America; military to military relations; foreign policy; international security; hegemony; militarisation; : Estados Unidos-América Latina; relações militares-militares; política externa; segurança internacional; hegemonia; militarização